Impact of COVID-19 infection among cancer patients treated at the Los Angeles County Medical Center. (2021) - Antrim, Lauren; Capone, Stephen; Dong, Stephen; Chung, David; Lin, Sonia; Wald-Dickler, Noah; In, Gino K.
Highlights: Increasing evidence suggests that patients with cancer diagnoses may be particularly vulnerable to poor outcomes from COVID-19. To our knowledge, this is the first such study to report on outcomes amongst a primarily Hispanic-American population of cancer patients with COVID-19. Elevated ANC, AST, CRP, and LDH at time of admission were significantly associated with severe outcomes. While the patients in our study received a variety of treatments, none were found to improve the occurrence of severe outcomes based on multivariate correlation analysis Abstract: We conducted a retrospective analysis of cancer patients who presented to the hospital with COVID-19 infection at a safety-net hospital in Los Angeles, California, from March 2020 to June 2020. From a list of 1, 163 COVID-19+ adult patients, we selected the first 50 patients with malignancy for a preliminary analysis. There were 23 males (46.0%) and 27 females (54.0%); the median age was 60.5 years (IQR 47 – 72). Thirty-nine (78.0%) of the patients were Hispanic. The most prevalent cancers were genitourinary (14, 28.0%), hematologic (11, 22.0%), and gastrointestinal (10, 20.0%). Twenty-one (42.0%) patients had active disease at COVID-19 diagnosis, while 25 (50.0%) had no evidence of disease (NED), and 4 (8.0%) were unknown. Over 1 in 3 admitted patients experienced a "severe outcome, " which was defined as critical level care (14, 34.1%), use of vasopressors (9, 22.0%), intubation (8, 19.5%), or death (5, 12.2%). Patients with severe outcomes were found to have statistically higher values of absolute neutrophil count ( p  = 0.005), aspartate aminotransferase ( p  = 0.049), high-sensitivity C-reactive protein, ( p  = 0.001) and lactate dehydrogenase ( p  = 0.040) on admission. Overall survival (OS) was not statistically different between those with hematologic versus solid malignancy nor between those with active disease versus remission (both p >0.05). Thirteen (81.3%) of the 16 patients who had cancer treatment in 2020 experienced delays in cancer therapy. Additional cases are being evaluated as the pandemic continues with the goal of identifying areas for potential intervention to improve outcomes in this at-risk population.